2013
DOI: 10.22610/jsds.v4i7.771
|View full text |Cite
|
Sign up to set email alerts
|

Project implementation success and Change Management practices in Malaysian Government-linked companies (GLCs)

Abstract: The purpose of this research is to address the practices of project change management in the context of Government-Linked Companies (GLCs) in Malaysia, focusing on Project Managers (PMs), Project Team Members (PTMs), Change Managers (CMs) and any other Top Managers involved in a project. Also, checking the validity of a number of critical success factors from Project Implementation Profile (PIP) in the context of GLCs in Malaysia. PIP is a comprehensive managerial tool that was introduced by Pinto and Slevin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…He determined that a project was successful if it met "business/organizational goals (i.e., product success) and functionality/schedule/budget, or functionality/schedule/budget adjusted for uncertainty (e.g., business change and project planning)" (p.274). Basamh et al (2013) applied Pinto and Slevin's 'diagnostic behavioral instrument' to examine project and change management practices in government linked companies in Malaysia. They found that there was a need for more consideration of human resources and resource allocation.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…He determined that a project was successful if it met "business/organizational goals (i.e., product success) and functionality/schedule/budget, or functionality/schedule/budget adjusted for uncertainty (e.g., business change and project planning)" (p.274). Basamh et al (2013) applied Pinto and Slevin's 'diagnostic behavioral instrument' to examine project and change management practices in government linked companies in Malaysia. They found that there was a need for more consideration of human resources and resource allocation.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…PPRISA helping in sustain the mechanism of project management such as; (1) a specific project management team, (2) important terms protecting the government and (3) to ensure the Service Level Agreement (SLA) clause in the contract and monitoring the achievement level of SLA. From the previous research on Project Management (PM) in Malaysia, researchers focused on government project failures from stakeholders' view [17], project and change management success factors [18], project implementation success and change management from government-linked companies [19] and CSFs from construction industries [20]. However, there is little evidence that emphasize solely on project planning perspectives in public sectors especially in Malaysian public sector.…”
Section: Project Management In Malaysian Public Sectormentioning
confidence: 99%
“…In the early stages of an IT project, no factor is as predictive of its success as support from senior management (Purna Sudhakar, 2012; Upadhyay et al, 2011). Authorizations and the willingness of senior management to be involved and to provide the necessary resources are the keys to successful implementation (Basamh et al, 2013). Indeed, when senior executives publicly support an IT project, the organization's members interpret these changes positively (Ifinedo, 2008).…”
Section: Managementmentioning
confidence: 99%
“…The right people have been selected for the organization (Dezdar and Ainin, 2012;Kuen and Zailani, 2009;Nah et al, 2007) α 5 0. Communication (COM) refers to the systematic planning, implementation, monitoring and review of all communication channels between everyone involved in the project (Almajed and Mayhew, 2014;Basamh et al, 2013;Kuen and Zailani, 2009) α 5 0.709, Rho_A 5 0.721, CR 5 0.837, AVE 5 0.632…”
Section: Ac1mentioning
confidence: 99%
See 1 more Smart Citation